True detective. Night country. [Season 4] [videorecording (DVD)] - López, Issa (Home Box Office, 2024)
In Season 4, Elizabeth Danvers and Evangeline Navarro, former partners, join forces to investigate the mysterious disappearance of eight scientists from the Tsalal Arctic Research Station in the fictional town of Ennis, Alaska. The story unfolds during the months-long winter nights, and as the two protagonists confront their own personal struggles, they delve into the eerie secrets hidden beneath the eternal ice to solve the complex case. The narrative explores the challenges of overcoming differences and facing the darkness within oneself.